Neerizhivu Kudineer- Action and Biochemical Analysis - Thirunarayanan, G.; Dharan, Binthuja G.; Sujatha, S. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Varmam is an art which includes martial arts, stimulation of Varma points, massage, Varma medicine and it is the part of Siddha system of medicine. Varma Maruthuvam is being used widely in south part of India especially Tamilnadu for various ailments. Ancient Varmam text indicates the trial drug Neerizhivu Kudineer for Neerizhivu (Diabetes mellitus). Aim of the study is to record the biochemical analysis of the trial drug Neerizhivu Kudineer. This study reveals presence of biochemical substances which helps to treat Diabetes mellitus and this drug will be effective against Neerizhivu (Diabetes mellitus).
Keywords: Neerizhivu Kudineer; Neerizhivu; Diabetes mellitus; Biochemical analysis